Mesoporous TiO2–SiO2 adsorbent for ultra-deep desulfurization of organic-S at room temperature and atmospheric pressure. Issue 14 (16th February 2018) - Qin, Bin; Shen, Yuesong; Xu, Boyang; Zhu, Shemin; Li, Peiwen; Liu, Youlin
Abstract : Ultra-deep desulfurization is a major requirement for upgrading the quality of fuel and power sources for fuel-cells. Abstract : Ultra-deep desulfurization is a major requirement for upgrading the quality of fuel and power sources for fuel-cells. A series of mesoporous TiO2 –SiO2 adsorbents were prepared and investigated for ultra-deep adsorption of benzothiophene (BT) and dibenzothiophene (DBT) from model fuel at ambient conditions. The adsorbents were characterized via SEM, XRD, N2 -BET, FT-IR and NH3 -TPD techniques. The results revealed that the adsorbent containing 40 wt% silica achieved the desulfurization efficiency higher than 99% when the initial sulfur concentration in the model fuel was 550 ppm. The high desulfurization performance of the adsorbent was attributed to its large specific surface and surface acidity. It also achieved a high sulfur adsorption capacity of 7.1 mg g −1 in a fixed-bed test, while its static saturated sulfur capacity was 13.7 mg g −1 . The order of selectivity towards the adsorption of different organic sulfurs was DBT > BT&DBT > BT. The kinetics of the adsorption of organic sulfur was studied and the results indicated that the pseudo-second order model appropriately fitted the kinetics data. Furthermore, the used adsorbent can be easily regenerated and the desulphurization efficiency of the recovered adsorbent after five regeneration cycles was still maintained at 94.5%.